Hurting all the way: The emotional antecedent and consequence of social rejection - Wang, Xiaoying; Li, Miaomiao (Frontiers in Psychology, 2022)
Social rejection is cold and hurtful, but how and why it is formed remains under-investigated. Our study offers one possible explanation from the rejector’s perspective by developing a moderated mediation model on the emotional antecedent and consequence of social rejection. Specifically, envious individuals use social rejection to complement their inferiority, further triggering their negative affect. Drawing on social comparison theory, we conducted an experience sampling methodology (ESM) investigation of 55 frontline workers through a ten-workday-survey (Level 1 n=515). As predicted, daily envy is positively associated with daily social rejection. Daily social rejection is positively related to daily negative affect. Furthermore, daily social rejection mediates the relationship between daily envy and daily negative affect. These effects are more robust for females than males, including the impact of envy on social rejection and the impact of envy on negative affect via social rejection. We suggest the recipient and the rejector make psychological and behavioral adjustments accordingly. We also recommend that future research extend our current study methodologically and theoretically.